1995
DOI: 10.1007/bf02332690
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive segmentation of burst-suppression pattern in isoflurane and enflurane anesthesia

Abstract: In this paper a developed novel algorithm for adaptive segmentation of Burst-suppression EEG is presented. The algorithm can detect bursts, suppression and artifacts, dividing the signal into corresponding segments. A compact representation of burst-suppression EEG, useful in monitoring long-term recordings, is presented. In the second part of the paper the burst-suppression patterns of isoflurane and enflurane anesthesia are compared. It is found that bursts as well as suppression segments are shorter in enfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…At least eight previous publications have presented methods for automated segmentation of burst suppression EEG patterns, based on a variety of EEG features and classification methods, including the nonlinear energy operator, spectral feature clustering, and neural-network classification of adaptive Hilbert-transformed EEG features (Thomsen et al, 1991; Lipping et al, 1995; Arnold et al, 1996; Griessbach et al, 1997; Sherman et al, 1997; Leistritz et al, 1999; Atit et al, 1999). These prior efforts are summarized and improved on in Särkelä et al (2002), the method most closely related to our method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least eight previous publications have presented methods for automated segmentation of burst suppression EEG patterns, based on a variety of EEG features and classification methods, including the nonlinear energy operator, spectral feature clustering, and neural-network classification of adaptive Hilbert-transformed EEG features (Thomsen et al, 1991; Lipping et al, 1995; Arnold et al, 1996; Griessbach et al, 1997; Sherman et al, 1997; Leistritz et al, 1999; Atit et al, 1999). These prior efforts are summarized and improved on in Särkelä et al (2002), the method most closely related to our method.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the results may not generalize to burst suppression EEG patterns of critically ill adults. Furthermore, validation of these methods against human expert clinical EEG segmentation has been limited (Thomsen et al, 1991; Lipping et al, 1995; Arnold et al, 1996; Griessbach et al, 1997; Sherman et al, 1997; Leistritz et al, 1999; Atit et al, 1999; Särkelä et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…The detection algorithm was trained on these 20 EEGs and showed high agreement compared to human annotations. Numerous other methods exist in literature that use various mathematical features to detect BSP (Thomsen et al, 1991; Lipping et al, 1995; Bruhn et al, 2000, 2006; Jaggi et al, 2003; Liang et al, 2014) but include a limited number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the duration of the suppression and burst epochs that were compared were only 2–6 s. A study in rabbits comparing 1 min each of EEG burst suppression during propofol and isoflurane anesthesia reported higher amplitude bursts during isoflurane anesthesia (Hartikainen et al, 1995a ). Another comparison between the burst suppression patterns of isoflurane and enflurane found that suppressions were shorter in duration for enflurane (Lipping et al, 1995 ). Burst suppression caused by hypoxic-ischemic encephalopathy has also been reported to have a higher variability in individual suppression durations compared to pentobarbital-induced burst suppression (Beydoun et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%